2019
DOI: 10.1590/abd1806-4841.20197797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-histopathological profile of the frontal fibrosing alopecia: a retrospective study of 16 cases of a university hospital

Abstract: Background: Frontal fibrosing alopecia is a condition of unknown origin, histologically similar to classic lichen planopilaris and generally observed in postmenopausal women with alopecia of the frontal-temporal hairline. oBjectives: To describe the clinical, dermatoscopic, and histopathological characteristics and the treatment used in patients who have frontal fibrosing alopecia at the Alopecia Outpatient Clinic in a university hospital. Methods: Retrospective descriptive study performed by reviewing medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(33 reference statements)
2
8
1
Order By: Relevance
“…When comparing present data with the literature, we observed a balanced division between Caucasians and Afro--descendants (p>0.05), which should reflect the great miscegenation of our population, as it can be seen in another Brazilian study. 17 Our data reflects a slightly earlier age of onset of FFA (52y) compared to the literature. 4,18 As in previous studies, most patients are postmenopausal, but unlike these, the prevalence of women under hormone replacement therapy is lower (28.6%) compared some reports.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…When comparing present data with the literature, we observed a balanced division between Caucasians and Afro--descendants (p>0.05), which should reflect the great miscegenation of our population, as it can be seen in another Brazilian study. 17 Our data reflects a slightly earlier age of onset of FFA (52y) compared to the literature. 4,18 As in previous studies, most patients are postmenopausal, but unlike these, the prevalence of women under hormone replacement therapy is lower (28.6%) compared some reports.…”
Section: Discussionsupporting
confidence: 69%
“…As for comorbidities, hypothyroidism was common among patients with FFA, with a lower prevalence than in other studies, 4,19 but similar to Brazilian studies. 17,21 In the authors experience, patients who were treated for FFA with doxycycline, hydroxychloroquine or finasteride had a slightly better control of the symptoms and clinical signs, such as positive pull test and pruritus, but progression seems to have its natural way and is limited to the natural history of the disease, which is still unknown. 7 Loss of body hair did not seem to be reversed or affected by treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to ours, a previous study by Secchin et al also reported an exclusively female patient population. 5 Zhang et al reported a population composed of 97% females, Kanti et al of 95% females, and Maldonado Cid et al of 97% females. 3,6,7 Recently, a case series of 7 male FFA patients has also been published; however, male patients are still a minority.…”
Section: Discussionmentioning
confidence: 98%
“…8 The result of this study in terms of gender distribution is in alliance with the previous literature: FFA is a disease that predominantly affects females. 3,[5][6][7] The increased prevalence of FFA in women especially in the postmenopausal period suggests the hormonal factors in disease pathogenesis. The role of sex hormones is not proven yet, while some studies found no correlation between sex hormones and FFA disease activity, in some studies, abnormal testosterone and estrogen values were found to be associated with lesser disease activity, and in a recent paper demonstrating that the serum levels of dehydroepiandrosterone sulfate (DHEAS) and an- drostenedione were significantly lower in FFA patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%